Effectiveness of Metcovasin Modern Dressing on Grade II Diabetic Ulcers: A Case Study - Ananda, Ribi; Amir, Haeril; Asnaniar, Waode Sri; Nurwahidah, Nurwahidah (PT.Mantaya Idea Batara, 2025)
Diabetic foot ulcers are among the most common complications experienced by individuals with diabetes mellitus, primarily caused by neuropathy (nerve cell damage). This study aimed to evaluate the effectiveness of modern alginate Metcovasin dressing in managing Grade 2 diabetic foot ulcers with impaired skin integrity. A case study design was employed. The intervention involved the application of modern alginate Metcovasin dressing for wound care in a patient with a Grade 2 diabetic ulcer at the ETN Centre Clinic in Makassar. The study was conducted on a single respondent. After establishing the nursing diagnosis, a wound care plan using modern alginate Metcovasin dressing was implemented once a week. Following the first week of treatment, notable improvements were observed, including reduced exudate (approximately 10%) and increased pink epithelial tissue (55%). By the second visit, the wound showed further improvement, with no exudate present and approximately 75% epithelialization. Based on the findings and nursing care provided, this study concludes that the use of modern alginate Metcovasin dressing is effective in promoting the healing process of diabetic foot ulcers.